Perception of medical students from the first to the sixth year and medical professors about vaccination in a Medical school (Research, Society and Development, 2022)
Vaccines are an important tool in the public health system. Since it is the physician's duty to guide patients about the importance of immunization, this research aims to analyze medical students' perceptions from the first to the sixth year and medical professors regarding vaccination in a private medical school UniCesumar in Maringá, Paraná. Therefore, a questionnaire was applied about general aspects of vaccination and the national immunization program (NIP). A total of 209 people responded to this research, 12 of them are professors and 197 are academics. Fisher's exact test and Kruskall-Wallis’s test were used for data analysis. As a result, all respondents agreed that the number of vaccines administered in the first year of life is not exaggerated, however, the researchers observed a great lack of knowledge about the main adverse effects after vaccination and how to act in the face of this event. Finally, the authors concluded that knowledge about immunization increases proportionally to the year of training and there is a lack of knowledge about AEPV.